Characterization and Structural Impact of Five Novel PROS1 Mutations in Eleven Protein S-deficient Families - Andersen, Bente Damm; Bisgaard, Marie Luise; Lind, Bent; Philips, Malou; Villoutreix, Bruno O.; Thorsen, Sixtus (Thrombosis and Haemostasis, 2001)
Heterozygozity for four novel missense mutations (W108C, W342R, E349K and L485S) and one novel 4 bp deletion (ACdelAAAG affecting codons 632-633) was identified in PROS1 of unrelated thrombosis prone Danish families with protein S type I or III deficiency. The 4 bp deletion results in a frameshift leading to replacement of the coding sequence for the 3 C-terminal amino acids by an abnormal extended sequence that codes for 9 amino acids. The E349K substitution was found in 7 families. Haplotype analysis using 7 microsatellite markers flanking PROS1 was consistent with a common founder for this mutation. The mutations reported here are most likely the cause of the protein S deficiency. Firstly, the four missense mutations cosegre-gate with the abnormal plasma protein S phenotype and lead to the loss of highly conserved amino acids. Secondly, computer analysis of structural models of protein S predicts that the substitutions could affect proper protein folding and/or stability. Analysis of platelet mRNA from subjects with the W108C, E349K, L485S mutation or the 4 bp deletion showed that mutated mRNA was expressed in significant amounts suggesting that mutated molecules are synthesized. Our results are compatible with defective protein folding/unstable molecules, impaired secretion and intracellular degradation of mutated protein, which appear to be the major molecular disease mechanisms for missense mutations and certain other mutations found in genetic disorders.
Keywords: Protein S mutations; venous thromboembolism; founder effect; structural analysis